Main belt asteroid collision histories: Cratering, ejecta, erosion, catastrophic dispersions, spins, binaries, tops, and wobblers. (15th September 2022) - Holsapple, Keith A.
Abstract: This is a study of the collisional history of the asteroids in the main asteroid belt. Over the ∼4.5 Byr of the belt existence, every asteroid collided with others a multitude of times, producing cratering, erosion, spin, fragmentation, reshaping, and occasional catastrophic disruption and dispersion. Extensive information for asteroid orbits, sizes, shapes, composition, and rotation states of those asteroids is now available. Those are a result of their history, but to interpret them requires understanding the processes. That understanding can be achieved by simulations of the history. A simulation needs robust models of the dynamical and collisional events. Such models have evolved substantially in the last few decades. Here I present extensive current models, a method, and a code "SSAH" (Stochastic Simulations of Asteroid Histories) for statistical recreations of the collisional history of the main belt. Although there are still significant gaps in our understanding of the necessary models, the code exposes those and gives a framework upon which existing and improved models can be tested. The results reveal new paradigms for asteroid histories, including the distribution of spins; the irrelevance of material strength spin limits; the 'uncommon' spins of such asteroids as the rapid rotating 2001 OE84, and of large slow spinning, tumbling object Mathilde; the "V-shape" in the spin versus diameter plot; the non-Maxwellian distributions of spins; the numbers of expected binaries and of tumblers, and more. They suggest a reassessment of the importance of the role of the YORP processes. The intent here is to provide current models, simulate the histories, note the uncertainties, and provide a framework for future improvements. The SSAH code is freely available for the use of others here, or directly from the author at holsapple@aa.washington.edu. Graphical abstract: Image 1 Highlights: A comprehensive stochastic modeling of the collisional histories of the asteroids in the main belt. A code ' SSAH' is developed and presented to simulate those histories. Models for the population, erosion, cratering, dispersions, spins, binaries, and tumblers. A novel explicit-implicit approach calculates specific explicit results for each target. New and perhaps controversial paradigms for asteroid histories.